2015
DOI: 10.1039/c4cc01190b
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast on-site selective visual detection of TNT at sub-ppt level using fluorescent gold cluster incorporated single nanofiber

Abstract: In this communication, a fluorescent gold cluster incorporated electrospun nanofibrous membrane and single nanofiber for selective and sensitive detection of TNT at sub-ppt level are demonstrated. This journal is © The Royal Society of Chemistry 2015

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 15 publications
1
32
0
2
Order By: Relevance
“…8.16. The fluorescence intensity is clearly decreased as a function of increasing concentration of TNT which is demonstrated by CLSM images [63] ( Fig. 8.16a-c).…”
Section: Fluorescent Electrospun Nanofibers For Explosive Detectionmentioning
confidence: 84%
See 1 more Smart Citation
“…8.16. The fluorescence intensity is clearly decreased as a function of increasing concentration of TNT which is demonstrated by CLSM images [63] ( Fig. 8.16a-c).…”
Section: Fluorescent Electrospun Nanofibers For Explosive Detectionmentioning
confidence: 84%
“…Anitha et al demonstrated selective, on-the-spot detection of TNT at sub ppt level using a single nanofiber embedded fluorescent gold clusters hybrid system [63]. They have incorporated red fluorescent BSA-capped gold clusters into the PEO nanofibers termed as Au.BSA@PEO-NFM using a simple and straightforward electrospinning method.…”
Section: Fluorescent Electrospun Nanofibers For Explosive Detectionmentioning
confidence: 99%
“…Along with these conventional methods, recently, several new techniques have been developed for detecting and assaying TNT, including colorimetry [16], surface-enhanced Raman spectroscopy (SERS) [17,18], fluorescence spectroscopy [19,20], and luminescent spectroscopy [21], among others. All of these methods enable a sensitive assay of TNT but require bulky expensive instruments, long assay time, and well-trained laboratory technicians.…”
Section: Introductionmentioning
confidence: 99%
“…The ideal electrode material should adsorb TNT and catalyze the electrochemical reduction of TNT. Many types of materials have been investigated for the electrochemical reduction of TNT, including various carbon materials (such as glass carbon [22], carbon nanotube [22], graphene sheet [19,23,25], nitrogen-doped graphene quantum dots [24], and boron-doped diamond [31]), gold [32], silica [33], and metal-oxides [34,35], etc. It has been determined that electrode materials with high adsorption ability for TNT can improve TNT detection sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated electrospun nanofibers as an excellent matrix for protecting and enhancing the sensing performance of fluorescent gold nanoclusters and metallic nanoparticles [22][23][24][25][26]. The polysulfone fiber-based membranes received much attention in the field ranging from artificial kidneys for blood purification to water treatment and food processing, owing to their good permeability, mechanical, thermal, and biocompatible properties [27,28].…”
Section: Introductionmentioning
confidence: 99%